Merging Whole‐cell Biosynthesis of Styrene and Transition‐metal Catalyzed Derivatization Reactions. Issue 6 (2nd February 2021) - Maaskant, Ruben V.; Chordia, Shreyans; Roelfes, Gerard
Abstract: The approach of combining enzymatic and transition‐metal catalysis has been focused almost exclusively on using purified, isolated enzymes. The use of whole‐cell biocatalysis, instead of isolated enzymes, with transition‐metal catalysis, however, has been investigated only sparsely to date. Herein we present the development of two transition‐metal catalyzed reactions used to derivatize styrene obtained from whole‐cell biosynthesis. Using a biocompatible ruthenium cross‐metathesis catalyst up to 1.5 mM stilbene could be obtained in the presence of E. coli, which simultaneously produced styrene. Using palladium catalysts and arylboronic acids, titers of up to 1 mM of several stilbene derivatives were obtained. These two transition‐metal catalyzed reactions are valuable additions to the toolbox of combined whole‐cell biocatalysis and transition‐metal catalysis, offering the possibility to supplement biosynthetic pathways with the chemical versatility of abiological transition‐metal catalysis. Abstract : Whole‐cell biocatalysis and transition‐metal catalysis combined : The whole cell biosynthesis of styrene was combined with a concurrent, abiological ruthenium catalyzed cross‐metathesis reaction to achieve the homocoupling of two styrene molecules. In addition, the biocatalytically produced styrene was converted into a range of stilbenes by a sequential palladium catalyzed cross‐coupling. These two transition‐metal catalyzed reactions are powerful tools, offering the possibility to supplement biosynthetic pathways with abiological transition‐metal catalyzed reactions.